Clinical Language Intervention Programme (KLISA PROGRAMME) to Improve Reading Skill of Students with Learning Disability with Potential in Education - Bungawali Abduh; Mohd Mokhtar Tahar; Mohd Hanafi Mohd Yasin (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
Reading is one of the fundamental skills across all subjects. A student with low competency in reading will experience difficulties in teaching and learning. The purpose of this research is to improve reading skills among student with learning disability in one secondary school in Bangi, Selangor. This action research had employed Reading Assessment Approach and descriptive analysis in data collection. Seven students with reading problem participated in this research. However, these students were having potential to be included in either Inclusive Program or Job Transition Program. Therefore, one reading program known as KLISA Program (Language Clinic Program) was created and it has been implemented in classroom for 30 minutes during the first period every day. This 9-month program had employed phonics method and used a set of ‘Bacalah Anakku’ books and ABM Velcro in three phases. The reading assessment was conducted at the end of each phase to evaluate the students’ achievement in reading. The findings of this research proved that KLISA Program was effective for students’ improvement in reading. Hence, it is recommended that this program can be consistently implemented to overcome illiterate and reading disorder among primary and secondary school students.Kemahiran membaca adalah merentas semua matapelajaran. Kelemahan dalam kemahiran membaca akan menyebabkan kesulitan mengikuti pengajaran dan pembelajaran. Tujuan penelitian ini adalah untuk meningkatkan kemahiran membaca di kalangan murid-murid bermasalah pembelajaran di sebuah sekolah menengah di Bangi, Selangor. Penelitian tindakan ini menggunakan pendekatan penilaian penaksiran bacaan dan analisis deskriptif untuk mengumpul data, Seramai 7 orang murid dalam sebuah kelas terlibat dalam kajian ini. Mereka terdiri dari murid bermasalah pembelajaran yang berpotensi untuk diserapkan di dalam Program Inklusif atau Transisi pekerjaan tetapi masih tidak boleh membaca. Satu program pemulihan bacaan iaitu Program KLISA (Program Klinik Bahasa) dilaksanakan selama 30 menit masa pertama sesi pengajaran setiap hari persekolahan. Pelaksanaan program ini menekankan kaedah fonik menggunakan set buku ‘Bacalah Anakku’ dan ABM Velcro serta dibuat dalam 3 gelungan yang mengambil masa 9 bulan. Penilaian bacaan dibuat setiap 3 bulan yang mewakili satu gelungan untuk melihat pencapaian murid dalam bacaan. Penilaian tersebut dibuat menggunakan satu set instrumen penilaian yang mewakili 8 tahap bacaan. Hasil penelitian membuktikan peningkatan kemahiran bacaan yang memberansangkan di kalangan murid-murid yang terlibat. Justeru itu disarankan program seumpamanya dilaksanakan secara konsisten bagi mengatasi masalah buta huruf dan tidak pandai membaca dikalangan murid-murid peringkat rendah dan menengah.DOI: http://dx.doi.org/10.17977/um029v4i12017p016